Enhancing External Skeletal Fixation Pin Performance: Consideration of the Pin-Bone Interface - Clary, E. M.; Roe, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
The integrity of an external skeletal fixator relies heavily on the pin-bone interface (PBI). Investigation of this interface have focused on histological, mechanical, thermal and clinical assessments. In this review the factors which are important for optimizing the strength and longevity of the PBI are presented. Pin design, pin insertion technique, bone quality and tissue response are considered.External skeletal fixation is used increasingly in human and veterinary orthopaedics. Pin loosening and infection are the primary causes of device failure and patient morbidity. Using several different techniques, researchers have identified a number of factors which affect the integrity of the pin-bone interface. These include pin design, pin insertion technique, initial bone quality and the osseous response to pin implantation and loading.
Keywords: Pin-bone interface; external skeletal fixation; fixation pin performance